The complexity of measuring interprofessional teamwork in the operating theatre. - Healey, A; Undre, S; Sevdalis, N; Koutantji, M; Vincent, C (2006)
Surgery depends on interprofessional teamwork, which is becoming increasingly specialized. If surgery is to become a highly reliable system, it must adapt and professionals must learn from, and share, tested models of interprofessional teamwork. Trainers also need valid measures of teamwork to assess individual and team performance. However, measurement and assessment of interprofessional teamwork is lacking and interprofessional team training is scarce in the surgical domain. This paper addresses the complexity of measuring interprofessional teamwork in the operating theatre. It focuses mainly on the design and properties of observational assessment tools. The report and analysis serves to inform the researcher or clinician of the issues to consider when designing or choosing from alternative measures of team performance for training or assessment.